Manajemen Risiko Investasi Untuk Mempertahankan Ketahanan Keuangan Di Tengah Volatilitas Pasar - Dela Wahyu Putri Awanda; Sevira Pahlevi Santoso; Maria Yovita R.Pandin (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research examines the impact of market volatility on investors' financial resilience and highlights the importance of investment risk management in maintaining financial resilience amid market volatility. Findings from 50 previous researchers show that sharp price fluctuations can undermine financial stability, especially for less experienced investors, and that investors in emerging markets are more vulnerable to speculative activity. To maintain financial resilience, effective risk management strategies are key. The research identified six key strategies: portfolio diversification, implementing stop-loss orders, rebalancing, dollar cost averaging (DCA), analyzing and managing risk through derivative instruments, and hedging. Each of these strategies has proven to help investors reduce risk, preserve capital, and cope with adverse market fluctuations. As such, a holistic risk management approach is necessary to protect financial resilience amidst increased market volatility.